Kitchen gardening - Nicholson, Rachel Gertrude (My University, 1905)
Introduction: The purpose of a kitchen garden is not the production of vegetables to supply the market but to supply the home table demand. In raising vegetables for home use the expenditure of time and money is amply repaid, and is well worth the effort. A kitchen garden is a necessity for every farm and is usually a possibility to the average town home except of course in the large cities. A good garden should furnish at least half of the family living for the entire year, and is thus an important means of support. Location; The kitchen garden should be conveniently near the kitchen, but soil, exposure to sun, and winds, drainage, and nearness to large trees are all subjects to be considered as well as convenience. If possible the garden spot should slope to the south or southeast, and there should be some protection from north winds, such as trees, providing they are not too near, a hill or even a good wall, or tight board fence. This protection will make considerable difference in time required for early vegetables to mature.
Citation: Nicholson, Rachel Gertrude. Kitchen gardening. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Hot Bed; Fermentation; Cold Frames; Theses; Manuscripts (documents)